Effects of workplace stress, perceived stress, and burnout on collegiate coach mental health outcomes - Wright, Simon A.; Walker, Lauren F.; Hall, Eric E. (Frontiers in Sports and Active Living, 2023)
Introduction Given the continuously changing job demands of coaches, coach burnout continues to be an important area of study. Coaching literature highlights the role occupational stressors play in the development and management of burnout. However, research highlights the potential need for the field to differentiate feelings of burnout from those of other sub-clinical mental health indicators (e.g., anxiety, depression). This study sought to examine the relationship between workplace stress, perceived stress, coach burnout, coach well-being, and sub-clinical health issues (anxiety, stress, depression). Methods One hundred forty-four NCAA collegiate coaches completed online questionnaires measuring the proposed variables. Structural equation modeling was used to test the proposed hypothesis that burnout would serve as a partial mediator between workplace and perceived stress and mental health indicators (e.g., depression, anxiety, stress, and well-being). Results Workplace stress and perceived stress were positively associated with both burnout subscales. Additionally, perceived stress alone exhibited a positive association with depression, anxiety, and stress and a negative association with well-being. While there was a positive significant relationship between disengagement and depression in the model and a negative significant relationship between disengagement and well-being, most relationships between the two burnout subscales and mental health outcomes were negligible. Discussion It can be concluded that while workplace and perceived life stressors may impact feelings of burnout and mental health indicators directly, burnout does not appear to exhibit a strong effect on perceptions of mental health and well-being. In line with other research studies, it may be worth considering whether burnout should be considered another type of clinical mental health issue instead of as a direct contributor to coach mental health.